Preliminary Evaluation of Diapause Intensity in Phytomyza orobanchia Kalt. (Diptera, Agromyzidae) in Faba Bean Vicia faba Fields in Alexandria, Egypt - Hegazi, Esmat; Khafagi, W. E.; Zeid, A. Abou; Attia, Manal A.; Hasaneen, Mervat; Shall, Amany Abu; Aly, Nagat; Taleb, H. K. Abou; El-Rahman, Safaa. Abd; Showiel, Sania F.; Al Eryan, M. Awad; Mahmoud, Anter K.; et al. (European Journal of Applied Sciences, 2024)
This study was carried out to evaluate the diapause intensity in Phytomyza orobanchia Kalt. (Diptera, Agromyzidae) in faba bean fields in Alexandria, Egypt. Several visits were carried out in faba bean seasons of 2021 and 2022 during January, February, March and April (cool to warm temperature) to collect spicks from faba bean fields infested by Orobanche crenata Forsk (Orobanchaceae). The spicks were dissected under binocular microscope and inspected for Ph.orobanchia puparia. Total of 6663 and 2810 Ph.orobanchia puparia were collected throughout the 1st and 2nd seasons, respectively. Ph.orobanchia puparia were allowed hatching to evaluate diapause incidence in the fly .Monthly mean fly emergence was recorded . This fly is a short-day species with a pupal summer - winter diapause. For each faba bean season, the onset of pupal diapause was in February increases in March and reached maximum in April. Large proportion of diapausing puparia of 1year old, hatched in January, decreased gradually, reaching its minimum in April. The live pupria that did not emerge after April, were assumed to be prepupae-pupae in diapause for more longer period (2-3 years). Also, large proportion of remaining diapausing puparia were found parasitized by Tetrastichus phytomyzae (Hymenoptera, Eulophidae) wasps. The emerged wasps were observed to parasitized the old unparasitized diapaused fly puparia and destroying the rearing fly culture during the two seasons. Females outnumber the males among non-diapausing flies. However, males outnumber the females for diapausing puparia hatched in March. While the sex ratio of emerged flies of diapaused puparia hatched in January, February and April was in favor of females.